Spatial Concepts RAUM, HAUS, ERDE, HIMMEL, WELTINNENRAUM in the Poetic Picture of the World R. M. Rilke - E. N. Aznacheeva (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
In the article, from the standpoint of cognitive poetics, the features of updating the RAUM conceptosphere in the poetry of R. M. Rilke are considered. The relevance of the study is due to insufficient knowledge of the phenomenon of the individual author’s conceptosphere of the poetic text, as well as the features of the functioning of text concepts in the work of R. M. Rilke. The objectives of the study are a layer-by-layer analysis of key artistic concepts in their relevance to the national language code, in identifying the functional characteristics of general cultural and individual-author elements of the concept sphere, in determining the cognitive-stylistic features of the poet’s idiollect. It is shown that the individual-author specifics of the RAUM conceptosphere by R. M. Rilke are distinguishing features of the categorization and specification of the semantics of concepts, whose names are the most common and significant lexemes with spatial semantics in the poet’s work. The significance of the spatial dimension in Rilke's poetry is indicated by the high recurrence of the exponents of the RAUM conceptosphere - the key concepts HAUS, ERDE, HIMMEL, WELTINNENRAUM together with other elements combined with them by synonymous, hyper-hyponymic and associative connection. It is proved that key concepts are a means of expressing personal meanings, the invariant content of which can be defined as the desire to overcome the limitations of earthly existence and to merge with a higher principle.